PENERAPAN KLAUSULA BAKU PADA PRASYARAT JUAL BELI JUNK FOOD DITINJAU DARI HUKUM BISNIS - Vivian, Fiona; Fitri, Winda (Universitas Ekasakti, 2022)
The phenomenon of junk food is growing rapidly at this time. Although most junk food ultimately harms the health of consumers, buying and selling junk food is not illegal. As a general rule, both the seller and the buyer are free to determine the type, content and form of the contract. However, the existence of standard clauses as a means to facilitate sales transactions between producers and consumers has proven to be widely misused by sellers with standard clauses that are detrimental to consumers, such as